Ocorrência de bactérias endofíticas na cultura do pinhão manso (Jatropha curcas L.) - Schmidt, Vitória Anselma (Universidade Federal de São Carlos, 2012)
The endophytic microorganisms inhabit the interior of the plants, being found in organs and tissues such as leaves, stems and roots without causing disease or producing visible external structures. The endophytic community consists mainly of bacteria and fungi that unlike pathogens, can benefit the plants, however, depending on conditions such as interaction between bacterial communities, competition for nutrients, it can become pathogenic. The endophytic community has been evaluated in many plants, especially in studies with diazotrophic bacteria. In this study, endophytic bacterial diversity of leaves, stems and roots of physic nut (Jatropha curcas) were studied using morphologic, physiological, biochemical and molecular markers, such as 16S rDNA. The samples were disinfected (removing epiphytic microorganisms), macerated and serially diluted to obtain the suspensions that were inoculated into culture media selective for diazotrophic microorganisms. The plates were incubated at 30°C for seven days. Forty-six colonie s were isolated, with 19 in the leaves, 11 in the stems and 16 in the roots. DNA of these endophytic bacteria purified was isolated, purified and the Y1-16S805 portion of the 16S rRNA gene was amplified and sequenced. Analysis of sequence identity were made by the programs BLASTn, CLUSTALW and phylogenetic analyzes by MEGA5. The roots showed greater diversity of endophytic microorganisms, with seven of the eight genera identified. In the leaves and in the stem, six genera were identified, respectively. In leaves, the exception was the genus Salmonella and Serratia. In the stem, Serratia, and in the roots more than one species of the genera Acinetobacter were found. The genera Bacillus and Burkholderia were found more frequently in all regions sampled. The genus Bacillus in the leaves, stems and roots accounted 20, 4 and 4%, respectively, of the total endophytic microorganisms identified. From the total isolates of the genus Bacillus, 73% belonged to the species B atrophaeus, B. brevis and B. sphaericus, the other 27% belonged to group B. cereus. These results suggest that the endophytic bacteria diversity of physic nut is large. Microorganisms identified in this work have potential for growth promotion, biological control and nitrogen fixation, as they were isolated in selective media with low concentration of nitrogen, in addition there are reports in the literature about the benefits of them for different plants.
Occurrence of endophytic bacteria in culture of physic Nut (jatropha curcas l.)
Keywords: Agroecologia; Bactérias endofíticas; Marcadores biológicos; Pinhão-manso; Crescimento (Plantas); Comunidade endofítica; Promoção do crescimento; Community endophytic; Morphological; Physiological, Biochemical and molecular markers; Physic nut; Promoting growth; CIENCIAS AGRARIAS